2011
DOI: 10.1002/esp.2127
|View full text |Cite
|
Sign up to set email alerts
|

A multi‐century record of linked nearshore and coastal change

Abstract: Using geographic information system (GIS) and field measurements the nearshore morphological variability of a headland bay beach at Tenby, West Wales (51·66 N; -4·71 W) was assessed over historical timeframes . Three areas chosen for detailed analysis were the area between mean low water (MLW) and lowest astronomical tide (LAT) contours; LAT and one fathom contours; and one and two fathom contours. Estuary closure c. 1855 has been suggested as the genesis for long-term beach evolution and did have an initial e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 20 publications
3
19
0
Order By: Relevance
“…Other variables also influence rotation, as shown by Anthony et al (2002) at Montjoly Beach, Cayenne, French Guiana, where patterns of nearshore mudbank migration induced rotation. Similarly, Thomas et al (2011b) linked beach diminution and migration, associated with spit collapse, to multi-century shoreline rotation within the current area of study.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Other variables also influence rotation, as shown by Anthony et al (2002) at Montjoly Beach, Cayenne, French Guiana, where patterns of nearshore mudbank migration induced rotation. Similarly, Thomas et al (2011b) linked beach diminution and migration, associated with spit collapse, to multi-century shoreline rotation within the current area of study.…”
Section: Introductionmentioning
confidence: 80%
“…Longshore sediment movement from south to north is influenced by heavily refracted Atlantic swell waves which undergo diffraction as they encounter the south Pembrokeshire coast and offshore Caldey and St Margaret's Islands. Gibbard (2005) estimated intertidal sediment loss of circa 7000 m 3 yr −1 , while Thomas et al (2011b) demonstrated that there was a reduction in updrift sediment input and downdrift leakage out of the system. The dune system (920 × 10 3 m 2 ) compensates for some of this loss through dune scarping during episodic events but, in general, extensive vegetation retards sediment movement from the dune field to the intertidal zone.…”
Section: Physical and Geological Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…On the Atlantic coast of Portugal, Dodet et al (2010) showed winter-averaged wave direction and the NAOw to be significantly correlated for the period 1953-2009. Thomas et al (2011aThomas et al ( , 2011b) also demonstrate linkages between NAOw, wind speed and direction, and the rotation of bay beaches in south Wales, UK. While variation in wave height is a clearly significant influence on beach morphology, beach rotation is more closely linked to oscillations in the dominant wind and wave direction between southwest and southeast quadrants.…”
Section: Contemporary Coast-climate Linkagesmentioning
confidence: 82%
“…Morphological responses of embayed beaches to storm and gale forcing have also been studied in the Northern [17][18][19] and Southern Hemispheres by amongst others [10,14]. The underlying causes of wave directional change have also been linked to subtidal mud bank and sandbank migration [20][21][22]. Unlike the macrotidal beach work carried out in this research, most rotation studies utilize variations in the location or volume of the subaerial zone to identify shoreline response; this was because almost all were studied in locations with microtidal or mesotidal ranges see for example [10,20,[23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%